A Comparative Study On Financial Performance Of Sbi In The Pre And Post Merger Periods Using Camels Rating Model - Jemima Jose; M Jegadeeshwaran (Perkumpulan Dosen Muslim Indonesia, 2024)
The core objective of the study aims to compare the performance of State Bank of India through CAMELS model during the pre and post merger periods with five of its associates. The study period covers 2012 to 2022. Data from secondary sources were used in this study. The comparison is made on the basis of the parameters like capital adequacy, asset quality, management quality, earning quality, liquidity and sensitivity to market risk. Data is analysed by using Paired sample t-test and also CAMELS ratings in the present study. The outcomes of the study reveals that SBI’s financial competency is improving post merger periods. But attention is required in liquidity quality in terms of total loans to total deposits (L1). Liquidity quality in terms of circulating assets to total assets (L2) and sensitivity to market are excellent in CAMELS ranking. Out of six parameters in CAMELS, management quality and liquidity quality in terms of total loans to total deposits (L1) are found to be significant in the post merger period. The study concluded that post-merger SBI's earnings quality is improved but liquidity did not. So management should be meticulous with managing liquid assets.